Protective effects of three luteolin derivatives on aflatoxin B1-induced genotoxicity on human blood cells - Orhan, Furkan; Ceker, Selcuk; Anar, Mustafa; Agar, Guleray; Arasoglu, Tulin; Gulluce, Medine (SPRINGER BIRKHAUSER, 2016)
In the present study, we aimed to investigate the genotoxic and anti-genotoxic potencies of three luteolin derivatives (luteolin-7-O-glucoside, luteolin-7-O-rutinoside and luteolin-7-O-glucuronide) by using human cells. In the micronucleus test, the human lymphocytes were exposed to aflatoxin B-1, the luteolin derivatives and a mixture of the two for 72 h. Furthermore, we have evaluated the levels of antioxidants of human whole blood plasma in order to clarify the possible mechanisms that may contribute to the anti-genotoxic activity of the luteolin derivatives. According to the results obtained from the micronucleus test, the highest protection rates for luteolin-7-O-glucoside, luteolin-7-O-rutinoside and luteolin-7-O-glucuronide against aflatoxin B1 were 32.09, 35.55 and 37.50 %, respectively. Similarly, these three luteolin derivatives ameliorated the level of antioxidants altered from aflatoxin B-1.
Keywords: Luteolin derivatives; Anti-genotoxic potential; Antioxidants; Micronucleus; DNA-DAMAGE; FLAVONOIDS; L.; ASSAY; OCHRATOXIN; SUPEROXIDE; METABOLISM; POTENCIES; CANCER; RISK; Pharmacology & Pharmacy